Histology Assessment of Chitosan–Polyvinyl Alcohol Scaffolds Incorporated with Cao Nanoparticles - Zapata-Ramirez, P (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Scaffolds for regenerative therapy can be made from natural or synthetic polymers, each offering distinct benefits. Natural biopolymers like chitosan (CS) are biocompatible and biodegradable, supporting cell interactions, but lack mechanical strength. Synthetic polymers like polyvinyl alcohol (PVA) provide superior mechanical strength and cost efficiency but are not biodegradable or supportive of cell adhesion. Combining these polymers optimizes their advantages while adding metal oxide nanoparticles like calcium oxide (CaO NPs) enhances antimicrobial properties by damaging bacterial membranes. In this study, we obtained the formation of CaO NPs by calcinating eggshells, which were mixed in a polymeric network of CS and PVA to obtain four different membrane formulations for subdermal tissue regeneration. The spherical nanoparticles measured 13.43 ± 0.46 nm in size. Their incorporation into the membranes broadened the hydroxyl bands in the Fourier transform infrared (FTIR) analysis at 3331 cm⁻1. X-ray diffraction (XRD) analysis showed changes in the crystalline structure, with new diffraction peaks at 2θ values of 7.2° for formulations F2, F3, and F4, likely due to the increased amorphous nature and concentration of CaO NPs. Additionally, higher CaO NPs concentrations led to a reduction in thermal properties and crystallinity. Scanning electron microscopy (SEM) revealed a heterogeneous morphology with needle-like structures on the surface, resulting from the uniform dispersion of CaO NPs among the polymer chains and the solvent evaporation process. A histological examination of the implanted membranes after 60 days indicated their biocompatibility and biodegradability, facilitated by incorporating CaO NPs. During the degradation process, the material fragmented and was absorbed by inflammatory cells, which promoted the proliferation of collagen fibers and blood vessels. These findings highlight the potential of incorporating CaO NPs in soft tissue regeneration scaffolds. © 2025 by the authors.